Effect of Fermented Wheat Gluten on the Physicochemical Properties of Soy Protein Isolate Films - Ruizhao JIANG; Yuan ZHAO; Linfan SHI; Zhongyang REN; Yucang ZHANG; Wuyin WENG (Shipin gongye ke-ji)
To improve the properties of soy protein isolate (SPI) films, composite films of wheat gluten (WG) and SPI were prepared with fermentation times of 0, 2, 4, 8 and 24 h. The effects of fermentation time on the physicochemical properties of the WG-SPI films were investigated through microstructural analysis of the material, Fourier transformed infrared spectroscopy, and measurements of mechanical properties, water vapor permeability and thermal stability. Spherical particles observed on the lower surface of the WG-SPI films gradually disappeared with increasing WG fermentation time. The WG-SPI films exhibited a dense network structure when WG was fermented for 4 h. The peak intensity of amide A in the WG-SPI films initially increased and then decreased as the WG fermentation time increased. With extended WG fermentation time, the intensity of the high-molecular-weight aggregate (HMWA) band in WG decreased, whereas that of the HMWA bands in WG-SPI films formed by drying first increased and then decreased. Over the fermentation period from 0 to 24 h for WG, the a* value of the WG-SPI films gradually increased from −3.24 to −2.84, while the b* value decreased from 15.02 to 12.19. The tensile strength, contact angle of the upper surface, and glass transition temperature of the WG-SPI films reached their maximum values—4.99 MPa, 99.67° and 59.73 ℃, respectively—when WG was fermented for 4 h. In contrast, the water vapor permeability, transparency value and solubility decreased to minimum values: 1.34×10−10 g·m−1·s−1·Pa−1, 2.11 and 6.42%, respectively. These results suggest that the addition of 4 h fermented WG significantly improves the physiochemical properties of SPI films, particularly in terms of tensile strength, water vapor permeability and thermal stability. This study provides a novel approach for enhancing the physicochemical properties of SPI films.